Introduction to film - Lacey, Nick (Palgrave Macmillan, 2005)
This concise introduction to the study of film offers an integrated and carefully paced overview of the issues and perspectives that contribute to a full understanding of the medium. It starts simply with a range of filmic examples, theoretical terms and analytical strategies chosen to reflect students' likely motivations for studing film in the first place. Its unified narrative line and student-centered philosophy create a layered approach, where greater complexity is built in stage by stage. It is enriched by a fund of diverse examples, handled as extended case studies or briefer vignettes, that offer a sensitive mix of the familiar, classic and more unusual.